ATC Bakery Online Booking System - Nazry, Nur Afryna; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2024)
The Online Booking Bakery System for ATC Bakery is a web-based platform developed using HTML, CSS, JavaScript, and PHP, with Adobe Dreamweaver as the development environment. The proposed system overcomes the current process that has been used manually and not efficient. The proposed system enables dynamic and interactive web pages, ensuring seamless user interactions and efficient data processing. The system’s cross-platform compatibility allows access from various devices and browsers, while real-time updates and a responsive interface enhance the customer experience. E-commerce functionality facilitates secure online transactions, providing a convenient platform for browsing, ordering, and making payments for bakery products. Secure online banking transactions and a reservation date/time feature align with personalized and on-demand services. Leveraging web programming languages and e-commerce capabilities, the system offers enhanced user experience, secure transactions, and operational efficiency. This revolutionizes the online bakery experience, establishing a robust platform for customers and administrators.